Identification of four genes required for mammalian blastocyst formation. Issue 3 (August 2014) - Maserati, Marc; Dai, Xiangpeng; Walentuk, Melanie; Mager, Jesse
Summary RNA transcription, processing and translation are fundamental molecular processes required for development, growth and cell viability. Towards the functional annotation of the genome, we are engaged in a reverse genetic screen using mammalian preimplantation embryos as a model system. Here we report the essential function of four RNA processing/splicing factors (Sf3b14, Sf3b1, Rpl7l1, and Rrp7a) and show that each of these genes is required for blastocyst formation in the mouse. As very little information is known about these genes, we characterized their normal expression and localization in mouse embryos as well as phenotypic analysis of loss of function during preimplantation development. Functional knockdown of each gene product results in normal morula development but there is failure to form a blastocoel cavity or morphologically differentiated trophectoderm. We show that zygotic genome activation does occur as well as initial lineage specification in the absence of each factor. Consistent with a role in RNA splicing, we demonstrate that the absence of Sf3b14 and Sf3b1 in 8-cell and morula-stage embryos results in a specific reduction of intron containing transcripts, but no reduction single-exon genes. Taken together, we show critical developmental and molecular requirements of Sf3b14, Sf3b1, Rpl7l1, and Rrp7a during mammalian preimplantation.